Meningkatkan Kompetensi dan Daya Saing Mahasiswa Melalui Pelatihan Pembenihan Ikan Bersertifikasi - Sara, La; Ngadiyo, Ngadiyo; Yusnaini, Yusnaini; Arsal, La Ode Muhammad; Annaastasia, Nurhuda; Wa Jali (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
"A certified Fish Hatchery Training program for students of the Faculty of Marine Science and Fisheries at Halu Oleo University was implemented to accelerate the improvement of student competency in aquaculture. This activity adopted a learning method that combined the delivery of educational material with hands-on practical experience in catfish (Clarias sp) hatchery techniques at the Aquaculture, Hatchery, and Fisheries Production Laboratory of FPIK UHO. This was facilitated by an outreach team and further integrated with an understanding of the catfish marketing aspects. Dividing the students into two groups during the hatchery practice sessions aimed to facilitate the active participation of each individual and allow for more focused supervision by the instructors. The training results indicated that the combination of theoretical education and direct practical experience in catfish hatchery techniques in the laboratory, along with instructor guidance, yielded significant learning outcomes